The Global Covid-19 Pandemic - Chidochashe Nyere (African Journal of Political Science)
The politics of science, or better still, the political science of global politics is what the world is battling, concerning the Coronavirus (Covid-19) pandemic, today. Whereas scientific disciplines such as virology and epidemiology would usually take centre stage when an outbreak such as Covid-19 strikes, and now owing to the vacuum that has been created by conflicting and contradictory information from health experts on Covid-19, global health is opened up to, or left up to, political giants. Health matters of virology and epidemiology surrounding Covid-19 have, thus, been reduced to issues of politicking. The World Health Organisation's voice (WHO), despite its sustained campaign and provision of information on Covid-19, is drowned and almost silenced by the number of health authorities and experts that have come out to refute mainstream information and strategies on combating and managing Covid-19. As such, the politicization of Covid-19 and the coloniality of knowledge and information surrounding Covid-19 may very well be the main issue of contention than the Covid-19 itself. This paper, therefore, seeks to unmask the political dimensions that are camouflaged by the Covid-19 pandemic and expose the real issues that Covid-19 has allowed to thrive and are, as a result, sustained by the Covid-19 crisis. Using the qualitative research methodology, I set out to discuss and analyse the debates on Covid-19 as have been proffered in the public domain. Thus, the method of research is a desktop analysis of academic articles, newspaper articles, social media pieces and mainstream television pieces, among others. I offer a decolonial account on Covid-19.